2010
DOI: 10.1128/aac.01414-09
|View full text |Cite
|
Sign up to set email alerts
|

Tigecycline Population Pharmacokinetics in Patients with Community- or Hospital-Acquired Pneumonia

Abstract: Tigecycline is a new-generation of tetracycline (glycylcyclines) and is active in vitro against bacteria that possess any of the classical genes that confer tetracycline resistance through ribosomal protection or efflux pumps. Herein, tigecycline disposition in patients with community-or hospital-acquired pneumonia was described using a population pharmacokinetic model. Additionally, the influence of covariates, such as body surface area, severity of illness, and clinical laboratory measures, on tigecycline di… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3

Citation Types

8
35
6

Year Published

2012
2012
2019
2019

Publication Types

Select...
8
1

Relationship

2
7

Authors

Journals

citations
Cited by 34 publications
(49 citation statements)
references
References 16 publications
(14 reference statements)
8
35
6
Order By: Relevance
“…The peripheral compartments of 8 HFSs were each inoculated with 20 ml of 6 log 10 CFU/ml M. abscessus. Treatment was administered daily for 21 days at doses that mimicked the non-proteinbound or free AUC 0 -24 , peak concentrations, and times to maximum concentration achieved in the lungs of humans treated with tigecycline doses of 0, 12.5, 25, 50, 100, 200, 400, and 800 mg, assuming linear increases in AUC 0 -24 with dose since clearance is constant over a range of doses (14)(15)(16). The doses were administered to the central compartment of each HFS once daily via computerized syringe pumps.…”
Section: Methodsmentioning
confidence: 99%
“…The peripheral compartments of 8 HFSs were each inoculated with 20 ml of 6 log 10 CFU/ml M. abscessus. Treatment was administered daily for 21 days at doses that mimicked the non-proteinbound or free AUC 0 -24 , peak concentrations, and times to maximum concentration achieved in the lungs of humans treated with tigecycline doses of 0, 12.5, 25, 50, 100, 200, 400, and 800 mg, assuming linear increases in AUC 0 -24 with dose since clearance is constant over a range of doses (14)(15)(16). The doses were administered to the central compartment of each HFS once daily via computerized syringe pumps.…”
Section: Methodsmentioning
confidence: 99%
“…where dose is equal to the total daily dose of tigecycline (100 mg) and CL T is the Bayesian post hoc clearance value generated from a previously conducted population PK analysis (6). In brief, the final population PK model was a two-compartment model with linear elimination.…”
Section: Methodsmentioning
confidence: 99%
“…Patient-specific PK parameter estimates were available from a population PK analysis of these data and were used to provide the most accurate estimates of exposure possible (6). These exposure estimates were indexed to the MIC of the infecting pathogen(s) and used to explore exposureresponse relationships for efficacy.…”
mentioning
confidence: 99%
“…Tigecycline was simulated with higher doses of 100 mg every 12 h and 200 mg every 12 h based on data from a murine pneumonia infection model, in which it was observed that the fAUC/MIC ratio was the pharmacodynamic parameter of importance predicting tigecycline efficacy against A. baumannii, and dosing regimens of Ն200 mg daily were required to achieve a 1-to 2-log reduction in organism density (25). Tigecycline pharmacokinetics were extrapolated from a study of patients infected with community-or hospital-acquired pneumonia (26) and used to simulate steady-state fAUC 0-12 exposures of 2.3 and 4.6 g · h/ml, as previously described (27). The targeted fC peak values were 0.6 g/ml and 1.2 g/ml for the 100-mg and 200-mg dosages, respectively, and protein binding was assumed to be 70%.…”
mentioning
confidence: 99%